2015
DOI: 10.1016/j.exphem.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of Hspa9 attenuate Stat5 activation in mouse B cells

Abstract: HSPA9 is located on chromosome 5q31.2 in humans, a region that is commonly deleted in patients with myeloid malignancies [del(5q)], including myelodysplastic syndromes (MDS). HSPA9 expression is reduced by 50% in patients with del(5q)-associated MDS, consistent with haploinsufficient levels. Zebrafish mutants and knockdown studies in human and mouse cells have implicated a role for HSPA9 in hematopoiesis. To comprehensively evaluate the effects of Hspa9 haploinsufficiency on hematopoiesis, we generated an Hspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Furthermore, in EVs associated with C. neoformans (live-BM-EVs and Hk-BM-EVs), higher levels of alarmin proteins, GRIA1, ARFGEF1/2, and HSPA9, were identified as shared components. These proteins are immunity modulators via pathways such as STAT5 ( 31 ). Notably, GRIA1, a regulator in glutamatergic signaling ( 32 ), and HSPA9, a stress-associated protein ( 33 ), were detected only in EVs from infected macrophages, suggesting specific roles in intercellular communication during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in EVs associated with C. neoformans (live-BM-EVs and Hk-BM-EVs), higher levels of alarmin proteins, GRIA1, ARFGEF1/2, and HSPA9, were identified as shared components. These proteins are immunity modulators via pathways such as STAT5 ( 31 ). Notably, GRIA1, a regulator in glutamatergic signaling ( 32 ), and HSPA9, a stress-associated protein ( 33 ), were detected only in EVs from infected macrophages, suggesting specific roles in intercellular communication during infection.…”
Section: Discussionmentioning
confidence: 99%
“…The level of HSPA9 expression and timing of deletion may be important for these phenotypes, as we have previously reported that constitutive heterozygous deletion of Hspa9 in mice does not result in cytopenias. [ 11 ] This suggests that compensation for a constitutive deletion of Hspa9 may occur during mouse development. HSPA1A, another Hsp70 family member, has been shown to regulate erythropoiesis by preventing active caspase-3 from cleaving GATA1 in the nucleus and inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ] In addition, complete loss of Hspa9 in mice is early embryonic lethal, suggesting that reducing HSPA9 levels below 50% may be lethal to cells. [ 11 ] Consistent with complete loss of Hspa9 being lethal, HSPA9 has recently been identified as an essential gene in human cells. [ 36 , 37 ] Inherited variants in HSPA9 have also been associated with congenital sideroblastic anemia with data suggesting >50% reduction is required to cause this phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heat-shock protein is involved in the translocation of proteins from the cytosol into the mitochondrial matrix, in the folding of such imported proteins and in the response to oxidative stress [ 44 , 45 ]. Deletion of the HSPA9 locus (5q31.1) is a frequent finding in myeloid malignancies [ 46 ]. In other settings, HSPA9 exhibits oncogenic properties, making it a potential therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%